2018
DOI: 10.1002/jcla.22402
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CXCL1 levels and TRAF3IP2 variants in patients with myocardial infarction

Abstract: The gene variants of Act1 adaptor are associated with correlates of poor outcome in patients with MI and plasma CXCL1 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…Further, CXCL-1 is associated with coronary artery calcium (CAC), aortic wall thickness and plaque burden. 49 Our results are in contrast to the circulatory CXCL-1 levels from other studies. This might be a compensatory response to the type 2 diabetes with coronary atherosclerosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, CXCL-1 is associated with coronary artery calcium (CAC), aortic wall thickness and plaque burden. 49 Our results are in contrast to the circulatory CXCL-1 levels from other studies. This might be a compensatory response to the type 2 diabetes with coronary atherosclerosis.…”
Section: Discussioncontrasting
confidence: 99%
“… 38–40 Plasma levels of CXCL1 are significantly increased in patients with AMI. 41 In the present study, we found negatively regulatory networks of miRNA–oxidative stress and prognosis-related mRNAs (hsa-miR-604-TLR4 and hsa-miR-139-5p-CXCL1) in AMI. This indicated that these miRNAs and targets play a crucial role in angiogenesis of AMI.…”
Section: Discussionsupporting
confidence: 54%
“…And the plasma levels of CXCL1 were significantly correlated with TT genotype of TRAF3IP2 (rs33980500) in myocardial infarction patients. [ 47 ] Whereas, CXCL8 may mediate the recruitment and activation of neutrophils, and promote the formation of new blood vessels. [ 48 ] In addition, CXCL8 is upregulated in the infarct area inducing polymorphonuclear leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%